Pharmacognostical Study of Guduchi Kanda Ghana Vati and Patra Ghana Vati (AYUSHDHARA, 2022)
Guduchi has Balya, Deepan-Pachana, Tridosha Shamaka and Rasayana properties. Ghana Vati is prepared from Guduchi kanda and Patra. As Patra of Guduchi is seldom used, its Ghana vati is prepared to find its efficacy in comparison to Kanda ghana vati in Madhumeha. Madhumeha is a leading disorder of the 21st century. In this disease the ligaments of the brain and spinal cord become weak. According to Ayurveda, Madhumeha is of two types: first occurs due to Dhatu kshaya janya prakupit vayu and the second one occurs due to Pitta evum kapha avrut vayu. In this present study pharmacognostical aspect of T. cordifolia is shown. Comparison is seen in the organoleptic characters and HPTLC and TLC of Kanda and patra ghan vati. Then the comparative effect of Guduchi kanda and Patra ghana vati will be observed in Madhumeha patients. Guduchi kanda ghan vati has been used earlier in Madhumeha but first time Guduchi patra ghan vati will be observed in such a situation.